1979
DOI: 10.1104/pp.63.3.436
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Molecular Weights of Proteins Synthesized by Isolated Chloroplasts with Those Which Appear during Greening in Zea mays

Abstract: (8,12,14,25) on the basis of their sizes. We have employed a discontinuous buffer system, which provides stacking of sample proteins, and a polyacrylamide gradient in the running gel to improve resolution of proteins over a wide range of mol wt further.Fluorography of the SDS-polyacrylamide gels was used to determine the number and mol wt of the membrane-associated products synthesized during incubation ofchloroplasts with radioactive amino acids. It is more difficult to quantitate amounts of radioactivity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 14 publications
(20 reference statements)
2
36
0
Order By: Relevance
“…CCCP, a commonly used inhibitor of photophosphorylation inhibits the incorporation by 50%o. Ellis and co-workers have found that CCCP totally inhibits protein synthesis in isolated chloroplasts, whereas with isolated etioplasts the inhibition was only 22% (6,29 The proteins synthesized in plastids isolated from the cotyledons of light-grown cucumber seedlings resemble those described by other workers using chloroplasts isolated from pea, spinach, or maize (12,13,22) (Fig. 5) Autoradiograph of the SDS-polyacrylamide gel profile of the translation products of the wheat germ system programmed with the same RNA as described in Figure 6.…”
Section: Resultsmentioning
confidence: 49%
“…CCCP, a commonly used inhibitor of photophosphorylation inhibits the incorporation by 50%o. Ellis and co-workers have found that CCCP totally inhibits protein synthesis in isolated chloroplasts, whereas with isolated etioplasts the inhibition was only 22% (6,29 The proteins synthesized in plastids isolated from the cotyledons of light-grown cucumber seedlings resemble those described by other workers using chloroplasts isolated from pea, spinach, or maize (12,13,22) (Fig. 5) Autoradiograph of the SDS-polyacrylamide gel profile of the translation products of the wheat germ system programmed with the same RNA as described in Figure 6.…”
Section: Resultsmentioning
confidence: 49%
“…Specific and absolute requirements for light during development were found for some thylakoid membrane polypeptides in greening etioplasts (13). At least one of these polypeptides, the apoprotein of CPI, is known to be synthesized by chloroplast ribosomes (4).…”
Section: Tionmentioning
confidence: 99%
“…Plastids develop that resemble chloroplasts of immature green fruit, except that many ofthe plastoglobuli formed during differentiation of chloroplasts to chromoplasts are still present in the redifferentiated chloroplasts (23). Development grown seedlings contain the chloroplastic proteins RuBPCase (18,22,27) and CF, (7). Upon exposure to light, etioplasts rapidly become photosynthetically competent chloroplasts, accumulating Chl, thylakoids, and new polypeptides including LHCP and CPI (1,18,26,27).…”
mentioning
confidence: 99%